Embodiment and fundamental motor skills in eSports - Van Hilvoorde, I.; Pot, N. (Sport, Ethics and Philosophy, 2016)
Electronic sports (eSports) and other variants of `digital sports` have increased in popularity all over the world and may even come to challenge hegemonic concepts of sport. More relevant than the apparent opposition between `physical` and `non-physical` is the question what kind of embodiment is manifested within virtual environments. In this paper, we argue that eSports do require the learning and performance of motor skills and that embodiment within a virtual environment may be considered playful or even athletic. The type of skills that might be tested can even be considered fundamental movement skills. Under appropriate educational supervision, with knowledge of the game, eSports can be utilized for the development of specific elements of digital literacy. Although motor skills are a defining characteristic of eSports, we do not argue that eSports should be integrated within PE. These arguments have not so much to do with the status of physicality present (or not), but with differences in type of interactions and possibilities for body contact. The visibility of movement behavior, of interactions and rule violations are intrinsically related to the social and pedagogical values of movement education. The direct and visible interaction between learners can be considered important pedagogical tools in PE, when the context of movement education is being understood as broader than just learning sport skills.